Contribution to the taxonomy and biodiversity of crustose lichens from the family Teloschistaceae - Frolov, Ivan Valerievich (Jihočeská univerzita, 2021)
The PhD thesis is composed of five published papers and one manuscript accepted for publication. The main research goal was the investigation of the taxonomy and diversity of crustose Teloschistaceae in Europe and Northern Asia with special emphasis on the genus Pyrenodesmia. The first paper investigated the delimitation of the genus Pyrenodesmia and its relationships with the closely related Caloplaca haematites and C. xerica groups and some other species. The second paper proposed standardized methods for the measurement of the morphological characters of the crustose Teloschistaceae and suggested a phenotype evaluation process for the delimitation of species that are difficult to phenotypically distinguish. The method was practically employed in the third paper for the separation of three seemingly cryptic species from the genus Pyrenodesmia, which were formally described in the paper. Another new Pyrenodesmia species was described in the fourth paper. Investigations presented in the fifth paper substantially extended the known geographical distribution of several species of crustose Teloschistaceae in Europe and Northern Asia. The accepted manuscripts proposes the description of the new species of crustose Teloschistaceae in Siberia and the Russian Far East. Our studies provide a basis for future summarizing papers on the taxonomy and diversity of the genus Pyrenodesmia in the Holarctic and the family Teloschistaceae in Russia.
Contribution to the taxonomy and biodiversity of crustose lichens from the family Teloschistaceae